Food mechanical properties and dietary ecology. (25th January 2016) - Berthaume, Michael A.
Abstract: Interdisciplinary research has benefitted the fields of anthropology and engineering for decades: a classic example being the application of material science to the field of feeding biomechanics. However, after decades of research, discordances have developed in how mechanical properties are defined, measured, calculated, and used due to disharmonies between and within fields. This is highlighted by "toughness, " or energy release rate, the comparison of incomparable tests (i.e., the scissors and wedge tests), and the comparison of incomparable metrics (i.e., the stress and displacement‐limited indices). Furthermore, while material scientists report on a myriad of mechanical properties, it is common for feeding biomechanics studies to report on just one (energy release rate) or two (energy release rate and Young's modulus), which may or may not be the most appropriate for understanding feeding mechanics. Here, I review portions of materials science important to feeding biomechanists, discussing some of the basic assumptions, tests, and measurements. Next, I provide an overview of what is mechanically important during feeding, and discuss the application of mechanical property tests to feeding biomechanics. I also explain how 1) toughness measures gathered with the scissors, wedge, razor, and/or punch and die tests on non‐linearly elastic brittle materials are not mechanical properties, 2) scissors and wedge tests are not comparable and 3) the stress and displacement‐limited indices are not comparable. Finally, I discuss what data gathered thus far can be best used for, and discuss the future of the field, urging researchers to challenge underlying assumptions in currently used methods to gain a better understanding between primate masticatory morphology and diet. Am J Phys Anthropol 159:S79–S104, 2016. © 2016 Wiley Periodicals, Inc.